2017
DOI: 10.1177/0033354917736514
|View full text |Cite
|
Sign up to set email alerts
|

Death Certification Errors and the Effect on Mortality Statistics

Abstract: Error rates on death certificates in Vermont are high and extend to ICD-10 coding, thereby affecting national mortality statistics. Surveillance and certifier education must expand beyond local and state efforts. Simplifying and standardizing underlying literal text for cause of death may improve accuracy, decrease coding errors, and improve national mortality statistics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
133
2
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(161 citation statements)
references
References 21 publications
6
133
2
5
Order By: Relevance
“…Death certificates are the basis from which disease prevalence data and national morbidity and mortality data are derived in the United States. 3,[11][12] Thus, death certification accuracy is key in ensuring that governmental prioritization of public health priorities and allocation of health funding for a multitude of conditions such as coronary heart disease, dementia, and various infections-to name a few-is appropriate. [13][14][15][16] Autopsy remains the standard against which clinician death certification accuracy is assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Death certificates are the basis from which disease prevalence data and national morbidity and mortality data are derived in the United States. 3,[11][12] Thus, death certification accuracy is key in ensuring that governmental prioritization of public health priorities and allocation of health funding for a multitude of conditions such as coronary heart disease, dementia, and various infections-to name a few-is appropriate. [13][14][15][16] Autopsy remains the standard against which clinician death certification accuracy is assessed.…”
Section: Discussionmentioning
confidence: 99%
“…This situation, a consequence of the division of powers, has introduced great variability in the practice of death classification generally, not just in the context of MAID. It is thus unsurprising that a search of the medical literature reveals numerous examples of studies demonstrating significant variability in the classification of the manner of death by various professionals (e.g., attending physicians, coroners and medical examiners) in response to scenarios [33].…”
Section: Resultsmentioning
confidence: 99%
“…One found an error rate of 39% in a national cohort including 336 deaths [23]; another conducted in selected Kansas City and St. Louis hospitals found an error rate of 45.8% [24]. A study in Vermont revealed that 51% of death certificates completed by non-medical examiners had major errors, and that certificates for hospital deaths were more error prone than those completed for residential deaths (59% vs. 39% errors) [25]. A nationally representative sample of older ­Americans who died while hospitalized found that there was significant disagreement between Medicare records and the assigned cause of death on certificates, and that the contributing nature of infections was under-reported [26].…”
Section: Discussionmentioning
confidence: 99%